Ocular Fundus Tumours: A Simplified Clinical Classification (Canadian Eye Care Today, 2024)
The diagnosis of the most common ocular fundus tumours can be achieved according to clinical features including their malignant potential, anatomical location within the eye, and relation to systemic disease, as well as imaging features. The majority of these tumours can be classified into four major categories according to their clinical presentation.